Analisis Kelayakan E-Magazine pada Submateri Peranan Bakteri Kelas X SMA - Sania, Rara; Yeni, Laili Fitri; Yuniarti, Anisyah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study aims to analyze the feasibility of an e-magazine on the inhibitory activity of Pontianak's siam orange peel extract against Bacillus cereus in the subtopic of bacterial roles. This research employs a quantitative descriptive method with several stages including e-magazine development, e-magazine validation, and data analysis. Validation activities consist of instrument validation by 2 validators and media validation by 5 validators. Validation was conducted using a closed-ended questionnaire validation sheet. E-magazine media validation assesses three aspects: format, content, and language. The validation results were analyzed using Aiken’s V formula and reliability testing using the Intraclass Correlation Coefficient (ICC). The study shows that the developed e-magazine meets Aiken’s V standard with a score of 0.92 and a reliability coefficient of 0.893, categorized as good, thus suitable for use as a learning medium. This e-magazine is complemented with appealing visualizations to provide a unique learning experience for students studying the bacterial roles subtopic.